2022
DOI: 10.3389/fonc.2022.873709
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Angiogenic Drugs Inhibit Interstitial Lung Disease Progression in Patients With Advanced Non-Small Cell Lung Cancer

Abstract: BackgroundInterstitial lung disease (ILD) is the most serious complication of chemotherapy in lung cancer patients with pre-existing ILD. The effect of anti-angiogenic drugs in lung cancer patients with ILD remains unclear. We examined the effect of anti-angiogenic drugs on reducing the risk of ILD progression in non-small cell lung cancer (NSCLC) patients receiving chemotherapy.MethodsWe analyzed the risk of ILD progression in 52 patients with advanced NSCLC with ILD who received first-line chemotherapy with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The anti-VEGF a antibody bevacizumab has been tested in patients with ILD and lung cancer and has been reported to prevent chemotherapy-induced AE-ILD [139,140].…”
Section: Chemotherapymentioning
confidence: 99%

Lung Cancer and Interstitial Lung Diseases

Drakopanagiotakis,
Krauss,
Michailidou
et al. 2024
Preprint
“…The anti-VEGF a antibody bevacizumab has been tested in patients with ILD and lung cancer and has been reported to prevent chemotherapy-induced AE-ILD [139,140].…”
Section: Chemotherapymentioning
confidence: 99%

Lung Cancer and Interstitial Lung Diseases

Drakopanagiotakis,
Krauss,
Michailidou
et al. 2024
Preprint
“…Pemetrexed or gemcitabine combined with platinum agents might be a feasible option for some patients with IPF and lung cancer [108]. Overall, irrespective of regimen, postchemotherapy-acute exacerbations have been observed in 8–13% of patients with the percentage rising up to even 30% in the Asian population [2,84 ▪▪ ,88 ▪ ,95,96,106,109].…”
Section: Which Chemotherapy/immunotherapy Regimens Are Beneficial For...mentioning
confidence: 99%
“…Interesting results were found following retrospective analysis of patients with fibrotic ILDs that received the monocloncal antibody against vascular endothelial growth factor-α (VEGF-α), bevacizumab. Combination of bevacizumab and chemotherapy regimens seemed to reduce the risk of chemotherapy-induced acute exacerbation-ILD in patients with ILD and lung cancer [88 ▪ ]. Another retrospective study suggested that the rate of ILD progression might be slower in patients with ILD and lung cancer treated with antiangiogenic compounds [89].…”
Section: Which Chemotherapy/immunotherapy Regimens Are Beneficial For...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, antiangiogenic therapy for cancer has been widely investigated in the development of novel drugs. 24,25 On the one hand, tumor growth requires tumor blood vessels to provide nutrients and oxygen, 26,27 and on the other hand, angiogenesis plays a remarkable role in tumor metastasis. [28][29][30] Interestingly, previous studies have suggested that metal thiosemicarbazone complexes exhibit excellent antiangiogenic activity.…”
Section: Introductionmentioning
confidence: 99%